Stereotip Gender Dalam Profesi Guru Pendidikan Anak Usia Dini - Dianita, Evi Resti (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2020)
The phenomenon of the scarcity of men to work as early childhood education teachers makes people assume that the profession is more suitable for women, so that there is an imbalance in gender roles in early childhood education institutions. But the discussion of gender issues surrounding the profession of early childhood education teachers still seems to often escape from our attention. This is the background for choosing this issue. The purpose of this study is to describe gender stereotypes in the early childhood education teacher profession and provide an alternative view of the importance of men's roles in this field. The approach used is a qualitative approach and the type is library research. Based on the discussion and analysis, it was concluded that gender stereotypes in the early childhood education teacher profession are at least tangible in three ways: a) existence of feminine identity attached to this profession and it is far from masculinity, so men are less interested in teaching young children; b) early childhood education teachers are considered as a profession with a minimum risk so that it is less challenging and considered more appropriate for women; c) early childhood education teachers are low-paid jobs and are considered more appropriate for women. Abstrak Fenomena langkanya laki-laki yang berprofesi sebagai guru pendidikan anak usia dini menjadikan masyarakat beranggapan bahwa profesi guru PAUD lebih sesuai untuk perempuan, sehingga terjadi ketidakseimbangan peran gender di lembaga PAUD. Namun pembahasan tentang isu gender yang mengitari profesi guru pendidikan anak usia dini tampaknya masih seringkali luput dari perhatian kita. Hal inilah yang melatarbelakangi dipilihnya isu ini. Tujuan dari penelitian ini adalah untuk mendeskripsikan tentang stereotip gender dalam profesi guru PAUD serta memberikan pandangan alternatif tentang pentingnya peran laki-laki sebagai guru PAUD. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan jenis riset kepustakaan. Berdasarkan diskusi dan analisis disimpulkan bahwa stereotip gender dalam profesi guru pendidikan anak usia dini setidaknya berwujud dalam tiga hal : a) pemberian identitas feminim dan jauh dari kesan maskulin, sehingga laki-laki kurang tertarik mengajar anak usia dini; b) guru PAUD dianggap sebagai profesi dengan minim risiko (low-risk) sehingga kurang menantang dan yang dipandang lebih sesuai untuk sektor ini adalah perempuan; c) guru PAUD adalah pekerjaan bergaji rendah dan dianggap lebih sesuai dilakukan oleh perempuan.